AI and popular culture - Barron, Lee, 1970- (SocietyNow., 2023)
"AI and Popular Culture explores the development and social significance of artificial intelligence by looking at representations in fiction, film and television, as well as examining the effect of AI technologies on the way we consume culture. Lee Barron traces the evolution of AI - from the Turing Machine to deep learning, to interrogate the key issues and debates. He uses examples of AI from pop culture to help us understand how the technology is changing aspects of society from surveillance and work to human relationships with technology. AI and Popular Culture sheds light on how artificial intelligence has changed our world and helps you to understand where it might take us next. It also makes significant contributions to Media and Cultural Studies, Humanities, and Social Sciences, as well as to subjects such as AI Ethics and Society and Computing."--